The Blessed Virgin and the Two Time-Series: Hervaeus Natalis and Durand of St. Pourçain on Limit Decision - Löwe, Can Laurens (Vivarium, 2017)
This paper examines the accounts of limit decision advanced by Hervaeus Natalis and Durand of St. Pourçain in their respective discussions of the sanctification of the Blessed Virgin. Hervaeus and Durand argue, against Aristotle, that the temporal limits of certain changes, including Mary’s sanctification, should be assigned in discrete rather than continuous time. The paper first considers Hervaeus’ discussion of limit decision and argues that, for Hervaeus, a solution of temporal limits in terms of discrete time can coexist with an Aristotelian continuous time solution because Hervaeus takes continuous and discrete time to be two non-intersecting, but correlated time-series. The paper next examines Durand’s account of limit decision and argues that Durand rejects Hervaeus’ correlation assumption as well as Aristotle’s continuous time solution.